Radiofrequency ablation of ventricular tachycardia in Anderson–Fabry disease: a case series. Issue 2 (4th February 2021) - Mills, Mark T; Nelson, Thomas A; Kelland, Nicholas F; Sahu, Jonathan; Lee, Justin; Lewis, Nigel; Hiwot, Tarekegn; Kyriacou, Andreas L
Abstract: Background: Cardiac involvement in Anderson–Fabry disease (AFD) can lead to arrhythmia, including ventricular tachycardia (VT). The literature on radiofrequency ablation (RFA) for the treatment of VT in AFD disease is limited. Case summary: We discuss RFA of drug-refractory VT electrical storm in three males with AFD. The first patient (53 years old) had extensive involvement of the inferolateral left ventricle (LV) demonstrated with cardiac magnetic resonance imaging (CMRI), with a left ventricular ejection fraction (LVEF) of 35%. Two VT ablation procedures were performed. At the first procedure, the inferobasal endocardial LV was ablated. Furthermore, VT prompted a second ablation, where epicardial and endocardial sites were ablated. The acute arrhythmia burden was controlled but he died 4 months later despite appropriate implantable cardioverter-defibrillator therapies for VT. The second patient (67 years old) had full-thickness inferolateral involvement demonstrated with CMRI and LVEF of 45%. RFA of several endocardial left ventricular sites was performed. Over a 3-year follow-up, only brief non-sustained VT was identified, but he subsequently died of cardiac failure. Our third patient (69 years old), had an LVEF of 35%. He had RFA of endocardial left ventricular apical disease, but died 3 weeks later of cardiac failure. Discussion: RFA of drug-refractory VT in AFD is feasible using standard electrophysiological mapping and ablation techniques, although the added clinical benefit is of questionable value. VT storm in the context of AFD may be a marker of end-stage disease.